Efektiftas Kelayakan Penyusunan Lembar Kerja Peserta Didik (LKPD) pada Pembelajaran Pendidikan Agama Islam di SMAN 1 Kecamatan Lareh Sago Halaban - Nisa Rama Dewi; Jasmienti Jasmienti (Moral : Jurnal kajian Pendidikan Islam, 2025)
The researcher conducted research at SMAN 1 Kecamatan Lareh Sago Halaban, sub-district, which was motivated by a learning process that still used learning resources that had not been adjusted to the feasibility of preparing these learning resources ptoperly the use of learning resourses that are less effective will of course hinder the smooth running of the learning process, the learning resourses used are based on student worksheets (LKPD) the fasibility of LKPD- based learning resources will greatly assist students in carryng out the learning process, especially in learning islamic religious education in class XI SMAN 1 Kecamatan Lareh Sago Halaban, this is because if the uses learning resources is adjusted to the fasibility of the preparation it will increases effectiveness in learning. The study aims to determine the effectiveness of the eligibility of studebt worksheets and the factors that challenge the fasibility of student worksheets learning resources in class XI SMAN 1 Kecamatan Lareh Sago Halaban. This type of research is desciptive quantitative. Data collection techniques with questionnaires, observasion and interviews.